Born in War: Canada's Postwar Engineers and Toronto's Ajax Division - Trudel, Jean-Louis (Scientia Canadensis, 1997)
ABSTRACTWith the start of the Second World War, the University of Toronto's Faculty of Applied Science and Engineering embarked on an unprecedented expansion that would eventually lead it to a wartime boomtown forty kilometers to the east of its downtown campus. For three and a half years after the war, returned men and women studied engineering in the converted barracks and buildings of the Ajax shell-filling plant. The stage for the postwar engineering boom, common to many Canadian universities, and especially Toronto's, was set during this time, and some of engineering's more enduring traditions at the University of Toronto may have been reinforced by the forced seclusion of the Ajax engineers as well as by the special treatment accorded to the overwhelmingly male veterans by the faculty and staff. In many ways, the story of Ajax Division is pivotal to understanding the training of engineers at the University of Toronto since the Second World War.